Pendampingan Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Berbasis Web Learning Kahoot! - Casmudi Casmudi; Sugianto Sugianto; Ryan Angga Pratama; Tutik Yuliani; Retnowaty Retnowaty (IKIP PGRI Bojonegoro, 2021)
ABSTRACTThe success of learning and its evaluation is determined by whether or not learning planning. Minister of Education and Culture Circular Letter Number 14 of 2019 states that the current lesson plan used by teachers is only 1 sheet and contains 3 core components, including Learning Objectives, Learning Activities, and Assessment. So teachers need to be up to date, and innovate in implementing learning activities, for example using Kahoot! which has several features including games, quizzes, discussions, and surveys. The Community Service Team (PkM) of the Faculty of Teacher Training and Education Balikpapan University realizes the need to increase coaching in the form of mentoring for teachers to compile and develop their One Sheet RPP independently. The results obtained were that the teacher felt greatly helped by the assistance and training in making One Sheet RPP which contained the Kahoot! in it, although not all teachers can complete it during the activity due to limited time and there will be further assistance from the Supervisor of the Education and Culture Office of Kutai Kartanegara Regency.Keywords: RPP, Kahoot!, learning ABSTRAKKeberhasilan pembelajaran beserta evaluasinya ditentukan dari baik atau tidaknya perencaan pembelajaran. Surat Edaran Mendikbud Nomor 14 tahun 2019 menyebutkan bahwa RPP saat ini yang digunakan guru hanya 1 lembar dan memuat 3 komponen inti, diantaranya Tujuan Pembelajaran, Kegiatan Pembelajaran, dan Penilaian. Sehingga guru perlu up to date, serta berinovasi dalam melaksanakan kegiatan pembelajaran, misalnya saja menggunakan Kahoot! yang memiliki beberapa fitur diantaranya game, kuis, diskusi, dan survey. Tim Pengabdian kepada Masyarakat (PkM) Fakultas Keguruan dan Ilmu Pendidikan Universitas Balikpapan menyadari perlunya peningkatan pembinaan berupa pendampingan bagi guru untuk menyusun dan mengembangkan RPP Satu Lembar secara mandiri. Adapun hasil yang diperoleh adalah guru merasa sangat terbantu dengan adanya pendampingan dan pelatihan pembuatan RPP Satu Lembar yang terkandung inovasi pembelajaran Kahoot! di dalamnya, meskipun tidak semua guru dapat menyelesaikannya selama kegiatan berlangsung dikarenakan terbatasnya waktu dan akan ada pendampingan lanjutan dari Pengawas Dinas Pendidikan dan Kebudayaan Kabupaten Kutai Kartanegara.Kata kunci: RPP, Kahoot!, pembelajaran